Gêneros do discurso em sala de aula: os casos do diário pessoal e da receita culinária - Campos, Elisa Silva (2010)
Since 1998, when the publication of Parâmetros Curriculares Nacionais de Língua Portuguesa do Ensino Fundamental II occurred, textbooks have tried to guide the studies of this subject with emphasis on interaction through language. This paper takes the study of genres as essential to education. Our dissertation stems from discussions that gave rise to the preparation of this document and the questions it raised in the academic and school fields. Taking the theoretical studies about language and about the kinds of speech made by the Bakhtin Circle and authors who publishes their contributions, our goal is to reflect on the text production of elementary school students in a private school in a city in the state of São Paulo. We selected 378 productions of recipes and personal diaries in order to verify how the subjectivity of the author-creator of these statements happens. The specific objectives of the research are: to reflect on possible changes in these genres when they migrate to the educational sphere; to contribute to a discussion about the artificiality of textual production at school; to determine how the student is placed as the author of their textual productions in this context. The specific objectives of this work are: to reflect on possible changes in these genres when they migrate to the educational sphere, contributing to a discussion about the artificiality of textual production at school, determine how the student is placed as the author of his textual productions in this context. The analysis developed shows that when gender is updated in the relationship of education, it changes, in particular by changes in interactive relationships that gives utterance. This change, however, does not occur only in the sense of “schooling” in the pejorative meaning of the term: in our corpus, this changing is a constitution of the author-creator of the production work of a statement to specific recipients, it’s a place for intersubjectivity in the new interactive situation. The contribution of this research lies in considering the updating of the genres of discourse in the classroom, not as "objects" of study but as "tools" for the study of language and discussion about the ways for the subject to act upon reality.